Lifestyle, socioeconomic disparities and intestinal microbiota in a sample of obese Egyptian women - Nayera E. Hassan; Salwa M. El Shebini; Sahar A. El-Masry; Nihad H. Ahmed; Nayra Sh. Mehanna; Mai M. Badie; Ahmed S. Ismail; Safinaz Megahed; Galal I. Elashry; Ayat N. Kamal; Mohamed S. Kishta; Heba T. Aboud (Journal of the Arab Society for Medical Research)
Background/Aim Obesity is caused by genetic and environmental factors, including cultural and societal influences on food intake and a decline in physical activity. This study aimed to assess the relationship between some lifestyle parameters and obesity and investigate the association between gut microbiota and both obesity and socioeconomic status in a sample of obese and normal Egyptian women. Patients and methods A cross–sectional study included 112 Egyptian women divided into two groups; 81 obese (BMI ≥30 kg/m2) and 31 normal women (BMI 18–<25 kg/m2) aged from 25 to 60 years. Anthropometric measurements, body composition, microbiota analysis, dietary history, socio-economic class, and lifestyle parameters were assessed. Faecal samples were obtained from all participants to determine gut microbiota and analysis of gene sequence using real-time PCR. Results The present result indicated significant differences (P<0.05) in both the anthropometric and body composition parameters among the obese and normal women. However, lifestyle parameters; including dietary intake, socioeconomic class, household crowding, sleep duration, internet usage, and physical activity have been shown to affect obesity. The low socioeconomic class participants had the lowest BMI (25.75±2.78 kg/m2) and the highest Firmicutes/Bacteroidetes ratio (0.83±0.01) with significant differences with the other socioeconomic classes. Obese participants consumed a significant over consumption of energy as a result of the over consumption of carbohydrates, fat and protein. While the mean daily vitamins and minerals intake were low, the highest percentage of the women in both groups were detected in the unsafe and unacceptable categories, especially for vitamins A, D, E, C, B6, B12, and folate, where the most deficient elements were zinc, calcium, and iron. Conclusion It was concluded that lifestyle parameters like dietary consumption intake with high caloric and fat contents, household crowding, long sleep duration, and internet usage were associated with obesity. Further data provided evidence that gut microbiota dysbiosis was associated with socioeconomic class rather than high BMI.